Nonaqueous, Mini-Dose Glucagon for Treatment of Mild Hypoglycemia in Adults With Type 1 Diabetes: A Dose-Seeking Study - Haymond, Morey W. (Diabetes Care, 2016)
OBJECTIVE: To evaluate mini-dose glucagon in adults with type 1 diabetes using a stable, liquid, ready-to-use preparation. RESEARCH DESIGN AND METHODS: Twelve adults with type 1 diabetes receiving treatment with insulin pumps received subcutaneous doses of 75, 150, and 300 μg of nonaqueous glucagon. Plasma glucose, glucagon, and insulin concentrations were measured. At 180 min, subjects received insulin followed in ˜60 min by a second identical dose of glucagon. RESULTS: Mean (±SE) fasting glucose concentrations (mg/dL) were 110 ± 7, 110 ± 10, and 109 ± 9 for the 75-, 150-, and 300-μg doses, respectively, increasing maximally at 60 min by 33, 64, and 95 mg/dL (all P < 0.001). The post–insulin administration glucose concentrations were 70 ± 2, 74 ± 5, and 70 ± 2 mg/dL, respectively, with maximal increases of 19, 24, and 43 mg/dL post–glucagon administration (P < 0.02) at 45–60 min. CONCLUSIONS: Subcutaneous, nonaqueous, ready-to-use G-Pen Mini glucagon may provide an alternative to oral carbohydrates for the management of anticipated, impending, or mild hypoglycemia in adults with type 1 diabetes.